Optimization of Quality of Service for a Cloud Gaming System using Layer Catching and Motion Prediction - Sadaike, Marcelo Tetsuhiro; Bressan, Graça (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
With the growing video games industry, new markets and technologies are emerging. Electronic games of the new generation are increasingly requiring more processing and powerful video cards. The solution that is gaining more prominence is Cloud Gaming, where the player performs a command, the information is sent and processed remotely on a cloud, then the images return as a video stream back to the player using the Internet. To improve the Quality of Experience (QoE), it is proposed a model that reduces the response time between the player command and the stream of the resulting game scenes through a game manager called Cloud Manager. The Cloud Manager uses layer caching techniques, in the background, and future state prediction, in the character, to reduce the network bandwidth usage, bitrate transmission and network latencies. The game is encoded in different layers, if a layer is the same in the following frame, it will not be re-encoded by the server. To speculate the next frames, the game manager renders all future possible outcomes based on the commands performed by the player.